(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the diagnostic information value of chlorin e6 fluorescence visualization of cancer lesion margins in the radical surgical removal of malignant lesions of the external nose. Material and Methods: Thirty patients were examined and underwent surgery for malignant cancer lesions of the external nose at the department for ear, nose and throat cancer during 2017 to 2020. Half of these patients (group 2) received and the rest (group 1) did not receive a preoperative injection of Klein solution and fluorescence visualization of cancer lesion margins. Results: Cancer lesion margins were visualized by fluorescence with chlorin e6 via deep green staining of tumor tissue. The tumor focus appeared violet, and the tumor periphery, crimson when chlorine-e6 fluorescence was excited with 630-633 nm light from a HeNe laser. Because there was no change in tumor lesion margins when compared with visualization without exposing the lesion to laser radiation, exposing the lesion to laser radiation is not mandatory. At three years after surgery, the non-recurrence rate was for 100% for the group of patients who underwent surgery with preoperative injection of Klein solution and fluorescence visualization of cancer lesion margins, and 73.4% for the group of patients who underwent surgery without chlorin e6 fluorescein visualization. Two years after primary surgery, 4 (26.6%) of group 1 patients were diagnosed with recurrent superficial cancer of the skin at the cartilage-bone interface. Conclusion: First, the recurrence rate was 26.6% (4 of 15 patients) for the group of patients who underwent surgery without chlorin e6 fluorescein visualization, which was significantly higher than for the group of patients who underwent surgery with chlorin e6 fluorescein visualization (0 of 15 patients, z = 2.091; р = 0.037). Second, the use of chlorin e6 fluorescein visualization of the margins of a skin lesion of the external nose in patients with malignant tumors of the external nose with tumor spread to the tissues of the medial angle of the eye and eyelid enabled a radical approach to surgical treatment to be employed in 100% of cases.